Solve Using the Square Root Property 5x^2+17x-12=0

Math
5×2+17x-12=0
Factor by grouping.
Tap for more steps…
For a polynomial of the form ax2+bx+c, rewrite the middle term as a sum of two terms whose product is a⋅c=5⋅-12=-60 and whose sum is b=17.
Tap for more steps…
Factor 17 out of 17x.
5×2+17(x)-12=0
Rewrite 17 as -3 plus 20
5×2+(-3+20)x-12=0
Apply the distributive property.
5×2-3x+20x-12=0
5×2-3x+20x-12=0
Factor out the greatest common factor from each group.
Tap for more steps…
Group the first two terms and the last two terms.
(5×2-3x)+20x-12=0
Factor out the greatest common factor (GCF) from each group.
x(5x-3)+4(5x-3)=0
x(5x-3)+4(5x-3)=0
Factor the polynomial by factoring out the greatest common factor, 5x-3.
(5x-3)(x+4)=0
(5x-3)(x+4)=0
If any individual factor on the left side of the equation is equal to 0, the entire expression will be equal to 0.
5x-3=0
x+4=0
Set the first factor equal to 0 and solve.
Tap for more steps…
Set the first factor equal to 0.
5x-3=0
Add 3 to both sides of the equation.
5x=3
Divide each term by 5 and simplify.
Tap for more steps…
Divide each term in 5x=3 by 5.
5×5=35
Cancel the common factor of 5.
Tap for more steps…
Cancel the common factor.
5×5=35
Divide x by 1.
x=35
x=35
x=35
x=35
Set the next factor equal to 0 and solve.
Tap for more steps…
Set the next factor equal to 0.
x+4=0
Subtract 4 from both sides of the equation.
x=-4
x=-4
The final solution is all the values that make (5x-3)(x+4)=0 true.
x=35,-4
Solve Using the Square Root Property 5x^2+17x-12=0

Download our
App from the store

Create a High Performed UI/UX Design from a Silicon Valley.

Scroll to top